Enzymatic Hydrolysis of Cane Bagasse (Saccharum sp hybrid) for the Production of Simple Sugars (Agroindustria, Sociedad y Ambiente, 2022)
Sugarcane bagasse (Saccharum sp hibrido) is a lignocellulosic agro-waste generated in large quantities by the sugar industry in Venezuela. The objective of this work was to obtain simple sugars by means of a physical pre-treatment and subsequent enzymatic treatment on the sugarcane bagasse. The method consisted of the use of Hot Water, at different temperatures and pressure on the bagasse. The sample with the best performance in terms of the release of its sugars was selected to which later, an Enzymatic Hydrolysis was applied using a commercial type cellulase preparation from the SIGMA brand Trichoderma Reesei fungus. The method with a temperature of 110 ºC, 15 Psi, was differentiated with exposure times of 40 and 60 min, resulting under these conditions an average of glucose released of 0.0346 and 0.0920 g / l. respectively. In the second condition, a temperature of 121 ºC, 15 Psi with times 40 and 60 min was used; achieving an average content of glucose released of 0.2936 and 0.2946 g /l. These results led to the selection of the condition of 121 ° C for 60 min, 15 Psi, which showed better results in the release of sugars, later it was subjected to enzymatic hydrolysis with cellulase, obtaining a final result of glucose concentration between 1.34 at 2.5 g / l.
Keywords: Cellulose; lignocellulosic residue; Trichoderma Reesei; cane bagasse